Discrimination between Leave of Apocynum venetum and Its Adulterant, A. pictum Based on Antioxidant Assay and Chemical Profiles Combined with Multivariate Statistical Analysis - Chi-On Chan; Ching-Ching Lau; Yam-Fung Ng; Li-Jia Xu; Si-Bao Chen; Shun-Wan Chan; Daniel Kam-Wah Mok (MDPI AG, 2015)
An integrated approach including chemical and biological assessments was developed to investigate the differences between Apocynum venetum L. (AV) and its adulterant, Apocynum pictum Schrenk (AP). Ten flavonoids were tentatively identified by ultra-visible and mass spectra data. The chemical component, hyperoside, was identified as a critical parameter for discrimination of two species from the results of principal component analysis (PCA) and quantitative analysis. The anti-oxidative power of the herbal extracts were determined using 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH) assay and H2O2-induced cell damage on LO2 cells. The results of the biological assays suggested that the chemical differences between AV and AP do lead to difference in activity and AV is demonstrated to have higher anti-oxidant activity.